Pedagogical Competence Effects on Students’ Self-Efficacy Using Rasch Model for Society 5.0 in Elementary School - Irni Rachmawati Putri (ALSYS, 2026)
This study is motivated by the limited research on the relationship between teachers’ pedagogical competence and students’ self-efficacy, particularly within the context of Society 5.0 in elementary education. This study aims to analyze the effect of teachers’ pedagogical competence on students’ self-efficacy. A quantitative research design was employed, involving elementary school students selected through random sampling. Data were collected using structured questionnaires and analyzed using the Rasch model to examine instrument validity, reliability, and the interaction between variables. The findings reveal that teachers’ pedagogical competence has a significant positive effect on students’ self-efficacy, supporting social cognitive theory, which emphasizes the role of environmental factors in shaping individual beliefs. These findings indicate that pedagogical competence plays a critical role in strengthening students’ confidence in learning, particularly in adapting to the demands of Society 5.0. This study contributes to the literature on pedagogical competence and self-efficacy by providing empirical insight into their relationship in digital learning contexts. Practically, the findings imply that educators and policymakers should enhance teacher training programs and integrate technology-based instructional strategies to support students’ learning confidence. Future research is recommended to examine the integration of other teacher competencies and conduct longitudinal analyses of students’ self-efficacy development.